In human resource management, performance appraisal systems in marketing and food company and in application - Özdemir, İrep Zehra (My University, 2005)
This study is consisted of three parts. In the first part, human resource functions are explained. It begins with the general definition of human resource management and then covers the activities of the major human resource functions such as; Job Analysis and Work Design, Human Resource Planning, Recruitment and Selection, Training and Development, Career Planning and Development, Performance Management, Compensation and Benefit. The second part consists of the explanation of the performance appraisal process in detail. It begins with general information about the evolution of performance appraisal, a seven-factor model and the steps in developing an appraisal system. Also, detailed information is given about the methods of performance appraisal management. For example; Work Standards, Rating Scales (Graphic Scales, The Checklist Appraisal, Forced Choice Rating Scales), Comparative Methods - Ranking (Alternation Ranking Method, Paired Comparison Method, Forced Distribution Method), Critical Incidents (Behaviorally Anchored Rating Scales, Behavioral Observation Scales), Essay Method, Multi-rater Assessment (360 Degree Feedback), The Management by Objectives, Mixing The Methods. Finally, the last part examines the usage of performance appraising system in a multinational firm. Information about MAP (Management Appraisal Performance) and its process are explained. The process of MAP is investigated in detail. Finally, the results of the usage of MAP process are given. Tez Özeti Bu çalışma üç bölümden oluşmaktadır. İlk bölümde, insan kaynakları fonksiyonları açıklanmaktadır. İnsan kaynakları yönetiminin genel tanımlanmasıyla başlamakta ve başlıca insan kaynakları fonksiyonlarının - İş Analizi ve İş Dizaynı, İnsan Kaynakları Planlaması, Seçme-Yerleştirme, Eğitim ve Geliştirme, Kariyer Planlaması ve Geliştirilmesi, Performans Yönetimi, Ücret ve Yan Gelirler açıklamalarıyla devam etmektedir. İkinci bölüm performans değerlendirme proseslerinin detaylı olarak açıklanmaktadır. İlk olarak, performans değerlendirme sisteminin oluşumuyla ilgili genel bilginin ardından, yedi-faktör modeli ve performans değerlendirme sisteminin geliştirilmesindeki adımlar açıklanmaktadır. Ayrıca, Performans değerlendirme yönetim metotları detaylı olarak incelenmektedir. Bu metodlar; İş Standartları, Oransal Ölçekler (Grafik Değerlendirme Skalaları, İşaretleme Listesi Yöntemi, Zorunlu Seçim Skalaları), Karşılaştırma Metodları - Sıralama Yöntemi (Değişken Sıralama Yöntemi, Eşli Karşılaştırma Yöntemi, Zorunlu Dağılım Metodu), Kritik Olaylar (Davranışa Dayalı Oran Skalaları, Davranışsal Gözlem Skalaları), Deneme Metodu, 360 Derece Değerlendirme, Hedeflere Göre Yönetim, Karışık Metodlar Yöntemi. Son bölümde, uluslar arası bir firmada performans değerlendirme sisteminin kullanımı incelenmiş, MAP sistemi ve işleyişi hakkında detaylı bilgi verilmiştir. Son olarak, kullanılan bu sistemin sonuçları ele alınmıştır.
Keywords: Genel yönetim; Personel Yönetimi